Efficient Water Management in Water Cooled Reactors. - Khamis, I. (International Atomic Energy Agency, 2012)
"In an effort to illustrate the sustainability of nuclear power, this publication discusses current practices on water requirements in nuclear power plants, possible future trends in design of water cooled reactors and the technologies employed. It analyses best practices and strategies for lower water withdrawal rates and presents the trade-off between production of electricity and water use and consumption, hence types of cooling systems to be selected. The book thus aims at enhancing the understanding of the issues related to water use, consumption, and management in a big picture."--Publisher's description.
"STI/PUB/1569"--Title page verso.
"August 2012"--Title page verso.
"Technical report"--Cover.
The IAEA officer responsible for this publication was I. Khamis of the Division of Nuclear Power."--Foreword.
Keywords: Water cooled reactors -- Management.; Nuclear power plants -- Water-supply.; elektronické knihy; electronic books